Molecular diversity of the invA gene obtained from human and egg samples - Mona Kadry (Veterinary World, 2019)
Background and Aim: Salmonellosis is one of the most common foodborne bacterial diseases in the world. The great majority of Salmonella infections in humans are foodborne with Salmonella enterica and Salmonella Typhimurium accounting for a major part of the problem. The objective of this study was to investigate the presence of invA gene in strains of Salmonellae isolated from eggs and diarrheal swabs from human cases. In addition, the relationship between invA gene nucleotide sequences from different sources (human stool and egg samples) have been studied through phylogenetic tree.